2024
DOI: 10.1021/acsnano.3c09499
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Precision: A Controllable Self-Synergistic Nanoplatform Initiating Pyroptosis-Based Immunogenic Cell Death Cascade for Targeted Tumor Therapy

Weiji Qin,
Lei Qiao,
Qian Wang
et al.

Abstract: Heterogeneity of the tumor microenvironment (TME) is primarily responsible for ineffective tumor treatment and uncontrolled tumor progression. Pyroptosis-based immunogenic cell death (ICD) therapy is an ideal strategy to overcome TME heterogeneity and obtain a satisfactory antitumor effect. However, the efficiency of current pyroptosis therapeutics, which mainly depends on a single endogenous or exogenous stimulus, is limited by the intrinsic pathological features of malignant cells. Thus, it is necessary to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
(79 reference statements)
0
0
0
Order By: Relevance
“…Previous studies have indicated that OVs can trigger tumor cell pyroptosis. , Pyroptosis is a form of inflammatory cell death characterized by cell swelling, membrane rupture, and the release of immunogenic substances. Pyroptosis is thought to be gasdermin-mediated programmed cell death. Notably, gasdermin E (GSDME)-mediated pyroptosis plays a critical role in the context of antitumor immunity . It has been shown that the expression level of GSDME is a determinant of the mode of transformed cell death and that spontaneous pyroptosis occurs only in tumors with high GSDME expression .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that OVs can trigger tumor cell pyroptosis. , Pyroptosis is a form of inflammatory cell death characterized by cell swelling, membrane rupture, and the release of immunogenic substances. Pyroptosis is thought to be gasdermin-mediated programmed cell death. Notably, gasdermin E (GSDME)-mediated pyroptosis plays a critical role in the context of antitumor immunity . It has been shown that the expression level of GSDME is a determinant of the mode of transformed cell death and that spontaneous pyroptosis occurs only in tumors with high GSDME expression .…”
Section: Introductionmentioning
confidence: 99%